Measurements of the branching fraction ratio B ϕ → μ + μ − / B ϕ → e + e − with charm meson decays - Aaij, R; Abdelmotteleb, ASW; Abellan Beteta, C; Abudinén, F; Ackernley, T; Adeva, B; Adinolfi, M; Adlarson, P; Agapopoulou, C; Aidala, CA; Ajaltouni, Z; Akar, S; et al. (Springer, 2024)
Measurements of the branching fraction ratio Bϕ→μ+μ−/Bϕ→e+e− with Ds+→π+ϕ and D+→ π+ϕ decays, denoted Rϕπs and Rϕπd, are presented. The analysis is performed using a dataset corresponding to an integrated luminosity of 5.4 fb−1 of pp collision data collected with the LHCb experiment. The branching fractions are normalised with respect to the B+ → K+J/ψ(→ e+e−) and B+ → K+J/ψ(→ μ+μ−) decay modes. The combination of the results yieldsRϕπ=1.022±0.012stat±0.048syst. The result is compatible with previous measurements of the ϕ → ℓ+ℓ− branching fractions and predictions based on the Standard Model.